Tradisi Protangen dan Perannya dalam Mempertahankan Etika Balas Budi - Heni Listiana; Sri Nurhayati; Zilfania Qathrun Nada (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study examines the resilience of the protangèn tradition in the Madurese community amid modernization, focusing on three aspects: its adaptation to change, its role in maintaining reciprocity ethics, and its relevance in modern society. Using a qualitative approach with in-depth interviews and participatory observation in Madura and its diaspora, the findings reveal that protangèn serves as a vital pillar in strengthening social solidarity and kinship ties, embodying moral values such as equality and mutual cooperation. Although modernization has transformed its practices—shifting toward financial aid or digital platforms—the tradition remains integral to Madurese life. A key challenge is declining participation among the younger generation, influenced by modern lifestyles. However, core values like reciprocity and solidarity persist. Preserving and promoting protangèn is crucial to ensure future generations uphold its ethical principles, even as its practices evolve with contemporary demands.